Novel nanostructured ternary metal oxide composite for sequestration of trace metals from simulated aqueous solutions. - Kupeta, Albert Jerry Kafushe (Vaal University of Technology, 2020)
A novel low-cost ternary Mn-Fe-Cu (MFC) metal oxide nanocomposite adsorbent was fabricated using facile co-precipitation method and successfully applied for the sequestration of Cr(VI) and As(III) from simulated aqueous efflent. The central composite design (CCD) of the response surface methodology (RSM) optimization technique determined the optimal working parameters for the preparation of the ternary MFC metal oxide nanocomposite. The spectroscopic microstructural analysis of the ternary MFC metal oxide nanocomposite was performed using fourier transform infrared (FTIR) spectroscopy, transmission electron microscopy (TEM), scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS) and X-ray diffraction (XRD) spectroscopy. The spectroscopic analyses revealed a rough surface with hydroxyl groups and the presence of mixed metal oxides in different valence states. The BET surface area, pore volume and pore size of the nanostructured MFC ternary metal oxide composite were found to be 77.2427 m2/g, 0.2409 cm3/g and 14.7560 nm, respectively. The pH drift method determined that the pHpzc of the adsorbent was 6.75. The batch technique was employed to investigate the adsorption dynamics (effects of ionic strength, co-existing anions, adsorbent regeneration and reuse) and optimum parameters (solution pH, adsorbent dosage concentration, desorption) of Cr(VI) and As(III) adsorption onto the MFC nanocomposite. The fitting of non-linear kinetic (pseudo-first-order, pseudo-second-order and Elovich), diffusion (intraparticle and Boyd) and isotherm (Langmuir, Freundlich and Dubinin-Radushkevich) models to the Cr(VI) and As(III) experimental adsorption data gave an insight into the adsorption mechanisms. The Langmuir adsorption capacities, qm (mg/g), were 168.71 at solution pH 3 and 35.07 at solution pH 9 for Cr(VI) and As(III) adsorption, respectively. The adsorption of Cr(VI) onto the ternary MFC metal oxide nanocomposite was physical and formed outer-sphere surface complexes through electrostatic interactions, while the removal of As(III) was specific due to inner-sphere surface complexation and ligand/ion exchange reactions. The results from XPS and FTIR analysis after the adsorption of Cr(VI) and As(III) showed that the surface hydroxyl groups on the MFC nanocomposite interacted with the Cr(VI) and As(III) species during the formation of the surface complexes. To facilitate ease of adsorbent removal from the treated simulated aqueous effluent, the ternary MFC metal oxide system was co-precipitated onto biochar support.
D. Tech. (Department of Chemistry, Faculty of Applied and Computer Sciences), Vaal University of Technology
Keywords: Aqueous solutions; Trace Metals; Metal oxide composite; Ternary nanocomposite; Central composite design; Response surface methodology; Mn-Fe-Cu (MFC); Transmission electron microscopy; Dissertations, Academic -- South Africa.; Nanostructured materials.; Nanocomposites (Materials).